An Analysis of Lexemic Idiomatic Expressions in Eaternal Nocturnal Webtoon - Sasqia Salsabilla Carishma; Zahrida Zahrida; Elfrida Elfrida (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2022)
This research aims to determine the types and meanings of lexemic idiomatic expressions in the Eaternal Nocturnal webtoon. This research used a qualitative method. The object of this research is the script of dialogues and narrations of the characters in Eaternal Nocturnal webtoon, namely episode two to episode six. The researcher used data sheets and tables as instruments. The researcher identified and categorized each expression based on Makkai's theory (1972) and using three dictionaries related to idioms, namely Farlex Dictionary of Idioms, Dictionary of American Idioms by McGraw-Hill's, and NCT's American Idioms Dictionary, then matched the meanings of lexemic idiomatic expressions from the dictionaries with the co-text contained in the dialogues or narrations of the characters to analyze the data. The results showed that there were six types of lexemic idiomatic expressions in the Eaternal Nocturnal webtoon, namely Phrasal Verb idioms, Tournure idioms, Irreversible Binomial idioms, Phrasal Compound idioms, Incorporating Verb idioms, and Pseudo idioms. In determining the meaning must be based on the co-text because an idiom contains many meanings. Keywords: Idiomatic, Lexemic Idiomatic Expressions, Webtoon